1975
DOI: 10.1073/pnas.72.3.1112
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of membrane lipids: mutants of Escherichia coli with temperature-sensitive phosphatidylserine decarboxylase.

Abstract: Phosphatidylserine decarboxylase catalyzes the last step in the pathway leading to phosphatidylethanolamine, the principal membrane lipid of E. coli. Mutants of E. coli have now been isolated in which this enzyme is thermolabile. The structural -gene for phosphatidylserine decarboxylase (psd gene) is closely linked to the purA locus at about -83 min on the standard map of the E. coli chromosome. When a mutant with thermolabile decarboxylase is incubated at 420, growth ceases, but only after a substantial fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 18 publications
(11 reference statements)
2
58
0
Order By: Relevance
“…Previous results demonstrated that LacY either expressed in cells or reconstituted into proteoliposomes showed a near absolute dependence for uphill transport activity, but not downhill transport activity, on an ionizable amino-based zwitterionic phospholipid [PE or phosphatidylserine (PS)] (9,10,18,19). LacY expressed in cells in which the neutral glycolipid monoglucosyl diacylglycerol (GlcDAG) (20) but not diglucosyl diacylglycerol (GlcGlcDAG) (21) replaced PE also carried out uphill transport.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results demonstrated that LacY either expressed in cells or reconstituted into proteoliposomes showed a near absolute dependence for uphill transport activity, but not downhill transport activity, on an ionizable amino-based zwitterionic phospholipid [PE or phosphatidylserine (PS)] (9,10,18,19). LacY expressed in cells in which the neutral glycolipid monoglucosyl diacylglycerol (GlcDAG) (20) but not diglucosyl diacylglycerol (GlcGlcDAG) (21) replaced PE also carried out uphill transport.…”
Section: Resultsmentioning
confidence: 99%
“…A temperature sensitive mutation in the psd locus was isolated by mutagenesis followed by brute force assay of individual colonies for PS decarboxylase (Psd) activity at an elevated temperature [63]. The initial mutant contained a second mutation, which rendered the cells temperature sensitive for growth but not for PS accumulation or lack of PE.…”
Section: Isolation Of Mutants In Phospholipid Metabolismmentioning
confidence: 99%
“…In bacteria and yeast, PS is synthesized by a PS synthase (PSS) that utilizes CDP‐diacylglycerol (CDP‐DG) and l‐ serine (Ser) as substrates (CDP‐DG‐dependent PSS or CD‐PSS; EC 2.7.8.8; Matsumoto, 1997). In Escherichia coli , PS is rapidly converted to phosphatidylethanolamine (PE) by PS decarboxylase (PSD), so that little PS accumulates in cells (Hawrot and Kennedy, 1975). However, E. coli psd ts mutants accumulate high PS levels at non‐permissive temperatures, leading to cell lysis (Hawrot and Kennedy, 1978).…”
Section: Introductionmentioning
confidence: 99%